NILAI–NILAI PENDIDIKAN ISLAM DALAM NOVEL 99 CAHAYA DI LANGIT EROPA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA DAN RELEVANSI TERHADAP DUNIA PENDIDIKAN ISLAM - Mahmudi Mahmudi; Imam Safi’i; Dian Mohammad Hakim (VICRATINA, 2022)
Novel 99 Cahaya di Langit Europe not only has the function of entertainment media, but can also be a medium in internalizing educational values, especially Islamic education. Proud to be a Muslim. The author tells about Muslims as a minority population on the European continent who find it difficult to maintain religious principles, but if their faith is strong they are able to survive and carry out Islamic Shari'a solemnly. Hanum and Rangga as Muslims try to carry out the mission of Islam as a religion of mercy. lil alamin not only to fellow Muslims aka but also to non-Muslims. Both depict the fruit of obedience to carry out orders and stay away from the prohibitions of Islam and do good to others, if there is a sense of tolerance among human beings.